Adaptive Function and Brain Evolution - Luis Puelles (Frontiers Research Topics, 2014)
The brain of each animal shows specific traits that reflect its phylogenetic history and its particular lifestyle. Therefore, comparing brains is not just a mere intellectual exercise, but it helps understanding how the brain allows adaptive behavioural strategies to face an ever-changing world and how this complex organ has evolved during phylogeny, giving rise to complex mental processes in humans and other animals. These questions attracted scientists since the times of Santiago Ramon y Cajal one of the founders of comparative neurobiology. In the last decade, this discipline has undergone a true revolution due to the analysis of expression patterns of morphogenetic genes in embryos of different animals. The papers of this e-book are good examples of modern comparative neurobiology, which mainly focuses on the following four Grand Questions: a) How are different brains built during ontogeny? b) What is the anatomical organization of mature brains and how can they be compared? c) How do brains work to accomplish their function of ensuring survival and, ultimately, reproductive success? d) How have brains evolved during phylogeny? The title of this e-book, Adaptive Function and Brain Evolution, stresses the importance of comparative studies to understand brain function and, the reverse, of considering brain function to properly understand brain evolution. These issues should be taken into account when using animals in the research of mental function and dysfunction, and are fundamental to understand the origins of the human mind.